San Jose State College Survival Faire
An image of a poster advertising the 10 year reunion of the Student Union at San Jose State University. The poster depicts two faces, one male and one female commenting on the celebration. The female asks the question "Why all the celebration in the student union, and the male responds "The Union is 10 years old! It's your party darling." Below the art is the caption: "Irving Norman's banquet upper level student union; 10th Anniversary Celebration! October 8-13, for more information call 277-3228."